Design Issues and Information Contents of the Provincial Government Websites of Indonesia: A Content Analysis on Visual Messages - Achmad Syarief; Agung Eko Budiwaspada; Irfansyah Irfansyah; Ifa Shafira Mustikadara (ITB Journal Publisher, LPPM ITB, 2009)
A website is not just merely act as an object of displaying information, but it also represents a contextual medium of communication through visuals and contents. The interplay of website design elements builds up meanings that affect users beyond what previous communication practices have uncovered. Previous research acknowledges that visuals and contents have significant effects in attracting users' attention and trust. Thus, the ability of a website to provide credible information through visuals and contents to target users is therefore plays great importance in the success of a website. However, although a considerable number of researches on website design have been performed, study in understanding the characteristics of site's visual appearances and information contents for the purpose of promoting local investment in Indonesia has been very limited. This paper addresses visual design issues and information contents of eighteen provincial government websites of Indonesia. Through content analysis, the paper comparatively examines visual appearances, information contents, and functions of each website, in order to determine visual characteristics and contents that suit the purpose of promoting local potencies. The paper focuses on commonality, discrepancy, and pattern of contents, provide suggestions to improve the use of provincial government website design of Indonesia.